PENGARUH SENAM HAMIL TERHADAP TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III DI PUSKESMAS PARIAMAN - YESI MAIFITA; YARNITA; SARI DARLITA YANA (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2026)
The third trimester of pregnancy often causes anxiety due to fear of childbirth, concerns about fetal safety, and psychological readiness as a mother. One non-pharmacological method that can be applied to reduce anxiety is pregnancy exercise. This study aimed to determine the effect of pregnancy exercise on anxiety levels among third trimester pregnant women at Public Health Center Pariaman in 2025. This research employed a pre- experimental design with a one group pre-test and post-test approach. The population consisted of all third trimester pregnant women in the working area of the Public Health Center Pariaman. A total of 16 respondents were selected using purposive sampling. The instrument used was the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data were analyzed using the paired sample t-test. The findings showed that before the exercise, most respondents experienced mild anxiety (56.3%), moderate anxiety (31.3%), and severe anxiety (12.5%). After the intervention, most respondents experienced mild anxiety (50%), some had no anxiety (31.3%), and a few experienced moderate anxiety (18.8%). No respondents experienced severe anxiety. The paired sample t- test showed a significant difference (p = 0.000; p < 0.05) with a mean difference of 6.438 points. Pregnancy exercise significantly reduces anxiety levels among third trimester pregnant women. It is recommended that health workers regularly conduct pregnancy exercise sessions and encourage pregnant women to actively participate to improve physical and psychological readiness for childbirth. Keywords: pregnancy exercise, anxiety level, third trimester, pregnant women